Increased CD4(+) CD25(+) T Regulatory Cell Activity in Trauma Patients Depresses Protective T(h)1 Immunity - MacConmara, Malcolm P. (2006)
OBJECTIVES: We recently reported increased CD4(+) CD25(+) T regulatory (Treg) activity after burn injury in mice. This study sought to determine if Tregs mediate the reduction in T(H)1-type immunity after serious injury in man and if Treg function is altered by injury. METHODS: Peripheral blood was withdrawn from 19 consenting adult patients (35.1 ± 16.3 years of age) with Injury Severity Scores (ISS) 36.6 ± 13.9 on days 1 and 7 after trauma and from 5 healthy individuals. CD4(+) T cells were purified and sorted into Treg (CD25(high)) and Treg-depleted populations. After activation of cells with anti-CD3/CD28 antibody, production of the T(H)1-type cytokine IFNγ, T(H)2-type cytokines (IL-4 and IL-5), and the inhibitory cytokine IL-10 was measured using cytometric bead arrays. Treg activity was measured by in vitro suppression of autologous CD4(+) T cell proliferation. RESULTS: All patients survived, 9 (47%) developed infection postinjury. IFNγ production by patient CD4(+) T cells was decreased on day 1 and day 7, when compared with healthy controls. However, when Tregs were depleted from the CD4(+) T cells, the IFNγ production increased to control levels. Tregs were the chief source of IL-4 and IL-5 as well as IL-10. Treg suppression of T cell proliferation increased significantly from day 1 to day 7 after injury. CONCLUSIONS: We demonstrate for the first time that human Tregs are increased in potency after severe injury. Most significantly, Tregs are important mediators of the suppression of T cell activation and the reduction in T(H)1 cytokine production found after injury.